Knowledge of Hepatitis B Virus Infection and Hepatitis B Vaccination Among Medical Students in a Tertiary Hospital in Jos, Plateau State, Nigeria - Okonkwo, Prosper Ifeanacho; Okafor, Kingsley C.; Lagasi, Eunice; Lamido, Saratu; Bamisaiye, Toluwani (European Journal of Applied Sciences, 2023)
Background: Hepatitis B virus is a potentially fatal infection that is one of the major public health problems around the world. It is important to affirm that medical students are future health care workers, and they will be at an increased occupational risk of contracting HBV infection from exposure to percutaneous and non-percutaneous injuries from using instruments containing infected blood during their clinical practice. This study seeks to assess the knowledge of Hepatitis B virus and Hepatitis B vaccination medical students in a Tertiary Hospital in Jos, Plateau State, Nigeria. Methods: This was a descriptive cross-sectional study done between March and August 2021 among 236 medical students using Stratified Sampling technique. Data was collected using a self-administered structured questionnaire and analysed using the IBM SPSS 28 (Statistical Package for the Social Sciences). Ethical approval was granted by Bingham University Teaching Hospital, Ethics Committee, Jos, Plateau State. Results: The majority 99.6% of the respondents have heard about HBV and 0.4% of the respondents have not heard about it. The majority got their information on Viral Hepatitis B from School (92.7%), and Hospital (72.8%). The Internet (61.2%,), Family/Friends (55.6%), and mass media (40.9%). Most respondents knew the mode of transmission, complications, asymptomatic clinical presentation, and curability. A majority had knowledge of existence of HBV Vaccine, willing to screen before test, 87.3% of respondents are of the opinion that HBV infected persons should not be vaccinated. Half 128 (54.2%) of the respondents had good knowledge of Hepatitis B infection and vaccination, 102 (43.2%) had fair knowledge, while 6 (2.5%) had poor knowledge. Conclusion: Above half of the students had good knowledge of Hepatitis B infection and vaccination, and a few had poor knowledge. There is a need to improve the general knowledge about hepatitis vaccine among students through teachings and participation in immunization activities and campaigns.